PENGARUH KOMUNIKASI GURU WALI KELAS TERHADAP PRESTASI SISWA SMPN 8 SURAKARTA - Nurnawati Hindra H, Farid Hidayat, Bedjo Sukarno & (Transformasi, 2016)
Master Class is the teacher that helps Principals to guide students in the discipline embodiesclass, as Manager and motivator to evoke a passion for beprestasi students in the/minat class.Good communication between teacher and student homeroom will have a major impact with thelearning achievements of students ' Research aims to find out whether there is influencecommunication master class student achievement against. Respondents research as many as 40children. Research methods are survey in which this research aims to test the hypothesis.According to Joseph a. Devito, Interpersonal communication is the process of sending andreceiving messages between two people or between a small group of people, with some effectsand some feedback instantly. Homeroom Teachers here as Communicators and students asKomunikan while Learning Achievements is as back feed. To answer these problems aboveauthor utilise the research field (field research). Method of data collection consists ofobservational methods, data processing, norm research, questionnaire, and draw conclusions.As for the formula used in the problem solving is the formula of using the formula ProductMoment. The formula is based on the authors can conclude that the appropriate calculation ofthe data processed by the correlation Coefficient using the formula Moment product. From theresults of the analysis of data obtained by the value of the correlation between influencecommunication teacher homeroom student achievement against 228 8 0,545 of Surakarta.Results analysis to the data consulted with table level correlation, whose value is between 0.600until 0.800.Based on the research of teacher walikelas (X) in the low category heading. Whilebased on student achievement SMP 8 Surakarta (Y) on the category heading. Then it can beknown based on Correlation table that the magnitude of the communication of the homeroomteacher against student achievement SMP 8 Surakarta is 0545. This means that there arepositive influences Influence communication between homeroom teacher against studentachievement SMP 8 Surakarta enough, then the hypothesis is accepted.Key Words: Interpersonal Communication, Master Class, Learning Achievements